Resigning in the face of disciplinary enquiry, or performance evaluation : reflections on a subsequent constructive dismissal claim - Setjie, Morake Samuel (My University, 2022)
Refer to the document
Thesis (LL.M. (Labour Law)) -- University of Limpopo, 2022
Keywords: Performance evaluation; Disciplinary enquiry; Resigning; Dismissal claim; Grievance procedures; Employees -- Resignation; Labor discipline; Employees -- Dismissal of